Volar Buttress Plating for Unstable Dorsal Fracture-Dislocations of the Proximal Interphalangeal Joint - Singh, Talvinder; Jayawardhana, Roshenka; Craigen, Michael; Rajaratnam, Vaikunthan (Journal of Hand and Microsurgery, 2019)
The authors present a series of 11 patients. All of them sustained an unstable dorsal fracture-dislocation of the proximal interphalangeal joint (PIPJ). These were managed with open reduction and internal fixation (ORIF) by use of an eight-hole, 1.3-mm oblique-angled strut plate, cut to shape to produce a four-hole plate, acting as a buttress plate. The operations were performed by orthopaedic surgeons with a special interest in hand surgery. Range of motion (ROM) and fixed flexion deformity (FFD) were measured postoperatively. Outcomes were assessed using the Quick Disabilities of the Arm, Shoulder and Hand (Quick-DASH) scoring system. Bony union, articular step-off, degenerative changes, persistent subluxation, or dislocation were confirmed by review of radiographs at latest follow-up. One patient developed a superficial infection and another developed complex regional pain syndrome. However, all patients were pain free at final follow-up. Radiographs at final follow-up confirmed bony union with no step-off, except for one patient who had a 1-mm step-off of the articular surface. Our attractive and novel technique of ORIF allows articular congruity to be restored anatomically with early active mobilization of the affected digit and early return to function.
Keywords: fracture; dislocation; proximal interphalangeal joint; internal fixation; buttress